An overview of psychology and law and forensic psychology in Australia - Allan, Alfred (2018)
Psychology’s roots in Australia go back to 1881, but the first documented evidence of psychology-and-law (psycholegal) research and psychologists working in court and correctional settings only emerged in 1949. The activities of psycholegal researchers and psychologists providing services to the correction, investigative and justice systems are not well-documented. Our aim in this paper is to start recording the histories of these people and the development of the psycholegal and forensic psychology fields. We do this primarily by examining publications and conference papers and recording our and other people’s personal recollections. We specifically record psychologists’ interaction with lawyers, their concerns about professional and ethical issues and the teaching of forensic psychology. We finally give a brief overview of the current state of the two fields